A Review on Numerical Simulation of the Selective Laser Melting Process: Mechanisms, Parametric Influences, and Future Directions - Liu, Chen; Cheng, Yiru (International Journal of Mechanical and Electrical Engineering, 2025)
Selective Laser Melting (SLM) is a leading additive manufacturing technology capable of producing complex metallic components with high precision. However, the intricate physical phenomena involved, such as rapid melting and solidification, lead to challenges in process control and quality assurance, often resulting in defects like porosity and residual stress. Experimental optimization is costly and time-consuming. Consequently, numerical simulation has become an indispensable tool for understanding the underlying mechanisms and optimizing process parameters. This review synthesizes recent research on the numerical simulation of the SLM process. It summarizes key findings on the modeling of melt pool dynamics, heat transfer, and fluid flow, highlighting the influence of primary process parameters—laser power, scanning speed, and hatch spacing—on the thermal behavior and resulting part quality. The paper discusses various modeling approaches, from continuum-based Finite Element Methods (FEM) to particle-level Discrete Element Methods (DEM), and the application of different heat source models. Key challenges, including multi-scale/multi-physics coupling, computational expense, and model accuracy, are identified. Finally, future research directions are proposed, emphasizing the potential of hybrid physics-based and data-driven models, and the integration of simulation with in-situ monitoring for real-time process control and defect prediction.